Cover page (Discussion Papers, 1993)
The tradition of fruitful relationship between Polish and Hungarian geographers looks back to several decades. In the scope of the scientific cooperation between the two Academies of Sciences bilateral seminars on different topics held every two years gained special importance. This volume includes the lectures of the 7th Polish-Hungarian Geographical Seminar organized by the Settlement Research Group of the Centre for Regional Studies in Kecskemét, Hungary in 1990. The topic of the seminar was the analysis of the socio-economic processes making way for the systemic change and the evaluation of spatial aspects of the initial steps. The majority of the lectures dealt with problems of the country level but some experts reported on their small-region investigations, and Eastern European countries other than Poland and Hungary were also mentioned. Thus the information contained in this volume is variegated and valuable. Undeniably, the lectures document a state that has changed by today, still, they can serve as bases of reference for the interpretation of changes later. According to their subject matter the eleven papers can be arranged round for topics: (1) General issues of regional policy (2) Industry and economy in the transitory period (3) The role of the tertiary sector and the services (4) Changes on the local level. The volume is published with the hope that it can promote a better understanding of regional development in Eastern Europe and that the interest of others than Polish and Hungarian geographers will be aroused.